Performance Comparison for Parabolic Dish Concentrating Solar Power in High Level DNI Locations with George Town, Malaysia - Ab Ghani, Mohd Ruddin; Affandi, Rosnani; Gan, Chin Kim (2013)
Parabolic Dish (PD), Concentrating Solar Power (CSP) generation has appeared as one of Renewable Energy (RE) that is efficient and trustworthy. As technology moves into commercialization, it is necessary to study the performance of PD system at various locations. Current literature on PD especially for tropical environment such as Malaysia and locations with Direct Normal Irradiance (DNI) lower than 1500kWh/m2/year is still scarce and scattered. Most of the studies are focusing on the performance at location with DNI higher than 2100 kWh/m2/year. Therefore, this paper presents the performance of PD in tropical environment of Malaysia and four other locations such as; Thailand, Korea, Australia and United States of America (USA). System Advisor Model (SAM) was used to analyze the performance of PD for selection countries. The simulation result shows that the annual energy production for George Town in Malaysia is 21,845kWh, and shows areas of high DNI have high power output such as Phoenix, USA 184,189kWh; Canberra, Australia 121,536kWh; Bangkok, Thailand is 48,736kWh and Inch'on, Korea 45,450kWh.